ҚАРАҚАЛПАҚ ФОЛЬКЛОРЫНДА ЛАП ЖАНРЫН ҮЙРЕНИЎДИҢ ƏҲМИЙЕТЛИ МƏСЕЛЕЛЕРИ - Бердимуратов, Ж. (SCIENCE and SOCIETY, 2021)
In Karakalpak oral art, lofts are very close to anecdotes in the essence of the genre. However, the use of strong expressions in them and their construction on the basis of dialogue distinguishes attics from anecdotes. Lofs are sung by most of the professional performers and are mainly represented in the repertoire of askia and amateur music. The article examines the genre features of these loaves, the sources of their origin, the stages of formation, the history of the development of literature.
Keywords: literature; folklore; art; improvisation; improviser; performers; humorist